Cortical Pathology in RRMS: Taking a Cue from Four Sisters. (27th September 2012) - Calabrese, Massimiliano; Seppi, Dario; Cocco, Eleonora; Poretto, Valentina; Rinaldi, Francesca; Perini, Paola; Gallo, Paolo
Abstract : Background . Although grey matter pathology is a relevant aspect of multiple sclerosis (MS) both with physical and cognitive rebounds, its pathogenesis is still under investigation. To what extent the familial and sporadic cases of MS differ in cortical pathology has not been elucidated yet. Here we present a multiple case report of four sisters affected by MS, all of them having a very high burden of cortical pathology. Methods . The clinical and grey matter MRI parameters of the patients were compared with those of twenty-five-aged matched healthy women and 25 women affected by sporadic MS (matched for age, disease duration, EDSS, and white matter lesion load). Results . Despite their short disease duration (<5 years), the four sisters showed a significant cortical thinning compared to healthy controls (P = 0.003 ) and sporadic MS (P = 0.041 ) and higher CLs number (P < 0.001 ) and volume (P < 0.001 ) compared to sporadic MS. Discussion . Although limited to a single family, our observation is worth of interest since it suggests that familial factors may account for a peculiar involvement of the cortex in MS pathology. This hypothesis should be further evaluated in a large number of multiplex MS families.